2023
DOI: 10.1021/acsbiomedchemau.2c00086
|View full text |Cite
|
Sign up to set email alerts
|

Live-Cell SOFI Correlation with SMLM and AFM Imaging

Abstract: Standard optical imaging is diffraction-limited and lacks the resolving power to visualize many of the organelles and proteins found within the cell. The advent of super-resolution techniques overcame this barrier, enabling observation of subcellular structures down to tens of nanometers in size; however these techniques require or are typically applied to fixed samples. This raises the question of how well a fixed-cell image represents the system prior to fixation. Here we present the addition of live-cell Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…We acknowledge that other methods of defining cell width include using the full width at half maximum (FWHM) across a line over the cell, as reported by Cao et al , Steifert et al , and Bednarska et al , 27,64–66 while using the longest distance of a cell for length measurement has been described by Yoda et al (2022). 28 We have chosen not to use FWHM method to avoid potential loss of information in the cell body, especially given our interest in comparing specific parts of the cell body before and after apoptosis. The width measurement adopted in our studies has been demonstrated by Osiro et al (2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We acknowledge that other methods of defining cell width include using the full width at half maximum (FWHM) across a line over the cell, as reported by Cao et al , Steifert et al , and Bednarska et al , 27,64–66 while using the longest distance of a cell for length measurement has been described by Yoda et al (2022). 28 We have chosen not to use FWHM method to avoid potential loss of information in the cell body, especially given our interest in comparing specific parts of the cell body before and after apoptosis. The width measurement adopted in our studies has been demonstrated by Osiro et al (2012).…”
Section: Resultsmentioning
confidence: 99%
“…Atomic force microscopy (AFM) is a label-free and well-established scanning probe microscopy (SPM) technique that offers high resolution imaging of the 3D topography of single cells, 27,28 but due to the likelihood of contact between the AFM tip and the cell membrane, imaging mammalian cell lines is challenging, as the cantilever tip can deform the cell membrane and only information about the cytoskeleton can be obtained. 29,30 SICM is a non-contact, non-invasive, and label-free SPM technique that uses a sharp nanopipette for studying the 3D topography of live cells in aqueous cell culture media under physiological conditions and with nanometer resolution.…”
Section: Introductionmentioning
confidence: 99%